Expression of the Androgen Receptor, pAkt, and pPTEN in Breast Cancer and Their Potential in Prognostication() - Sultana, Aisha (Neoplasia Press, 2014)
BACKGROUND: Importance of androgen receptor (AR) as an independent prognostic marker in Pakistani women with breast cancer (BCa) remains unexplored. Our aim was to identify the expression and potential prognostic value of AR, its upstream regulator (pAkt) and target gene (pPTEN) in invasive BCa. METHODS: This study used a cohort of 200 Pakistani women with invasive BCa diagnosed during 2002-2011. Expression of AR, pAkt and pPTEN was determined on formalin fixed paraffin embedded tissue sections by immunohistochemistry. The association of AR, pAkt and pPTEN with clinicopathological parameters was determined. Survival analyses were undertaken on patients with ≥ 5 years of follow-up (n = 82). RESULTS: Expression of AR, pAkt and pPTEN was observed in 47.5%, 81.3% and 50.6% of patients, respectively. AR-expressing tumors were low or intermediate in grade (P < .001) and expressed ER (P = .002) and PR (P = .001). Patients with AR(+) tumors had significantly higher OS (Mean OS = 10.2 ± 0.465 years) compared to patients with AR(−) tumors (Mean OS = 5.8 ± 0.348 years) (P = .047). Furthermore, AR-positivity was associated with improved OS in patients receiving endocrine therapy (P = .020). Patients with AR(+) /pAkt(+) /pPTEN(−) tumors, had increased OS (Mean OS = 7.1 ± 0.535 years) compared to patients with AR(−)/pAkt(+)/pPTEN(−) tumors (Mean OS = 5.1 ± 0.738 years). CONCLUSION: AR-expressing tumors are frequently characterized by low or intermediate grade tumors, expressing ER and PR. In addition, expression of AR, pAkt and pPTEN, could be considered in prognostication of patients with invasive BCa.